Language Use: An Analysis of Directive Acts Used by Eleventh Grade Students at SMAN 4 Singaraja - ., Mas Mirah Dewi Ni Gusti Ayu Kade; ., Prof. Dr. Dewa Komang Tantra,Dip.,App.; ., Luh Diah Surya Adnyani, S.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Penelitian ini bertujuan untuk menganalisa jenis directive acts, gaya, kesalahan yang dibuat, dan sumber kesalahan yang dilakukan oleh siswa kelas sebelas di SMAN 4 Singaraja. Penelitian ini adalah penelitian deskriptif kualitatif. Subjek dari penelitian ini adalah 32 siswa. Instrument yang digunakan adalah perekam, catatan, dan sebuah pedoman tanya jawab. Hasil dari penelitian ini menunjukkan bahwa ada tujuh jenis directive acts yang digunakan oleh siswa. Diantaranya (1) to request berjumlah 220 (22.9%), (2) to order berjumlah 496 (51.7%), (3) to permit berjumlah 23 (2.4%), (4) to ask berjumlah 7 (0.7%), (5) to advise berjumlah 35 (3.6%), (6) to pray berjumlah 21 (2.2%), (7) to invite berjumlah 14 (1.4%) dan (8) klasifikasi berbeda berjumlah 144 (15%). Selain itu, siswa menggunakan gaya resmi dan tidak resmi, diantaranya (1) to request formal berjumlah 24 (2.50%), (2) to request informal berjumlah 196 (20.41%), (3) to order formal berjumlah 6 (0.62%), (4) to order informal berjumlah 490 (51.04%), (5) to permit formal berjumlah 5 (0.52), (6) to permit informal berjumlah 18 (1.87%), (7) to ask informal berjumlah 7 (0.71%), (8) to advise formal berjumlah 3 (0.31%), (9) to advise informal berjumlah 32 (3.33%), and (10) to pray informal berjumlah 21 (2.20%). Terdapat 8 kesalahan penggunaan kata dan 52 grammar dalam data yang ditemukan. Kesalahyan tersebut dikategorikan kedalam interference dan developmental error.Kata Kunci : Kata Kunci: directive acts, style, and error bstract This study aimed at analyzing the types of directive acts, the style, the errors committed and the sources of errors by eleventh grade students at SMA N 4 Singaraja. This study is a descriptive qualitative research. The subject of this study are 32 students. The instruments used in this study are tape recorder, a field note, and an interview guide. The results of this study show that there are six types of directives act used by students. They are (1) to request had the number was 220 (22.9%), (2) to order had the number was 496 (51.7%), (3) to permit had the number was 23 (2.4%), (4) to ask had the number was 7 (0.7%), (5) to advise had the number was 35 (3.6%), (6) to pray had the number was 21 (2.2%), and unclassified categorize had the number was 158 (16.5%). Moreover, the students use formal and informal style, they are (1) to request formal was 24 (2.50%), (2) to request informal was 196 (20.41%), (3) to order formal was 6 (0.62%), (4) to order informal was 490 (51.04%), (5) to permit formal was 5 (0.52), (6) to permit informal was 18 (1.87%), (7) to ask informal was 7 (0.71%), (8) to advise formal was 3 (0.31%), (9) to advise informal was 32 (3.33%), and (10) to pray informal was 21 (2.20%). In those data there are 8 errors on diction and 52 errors on grammar. The errors are categorized as interference and developmental error. keyword : Key Words : directive acts, style, and error